2020
DOI: 10.7762/cnr.2020.9.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chromium Picolinate Supplementation on Cardiometabolic Biomarkers in Patients with Type 2 Diabetes Mellitus: a Randomized Clinical Trial

Abstract: Type 2 diabetes mellitus (T2DM) is a serious public health problem accompanies with several complications. This study was conducted to evaluate the effects of chromium picolinate (CrPic) supplementation on the glycemic status and lipid profile in patients with T2DM. The patients with T2DM (n = 52) were randomly allocated into 2 groups. One group received 400 µg CrPic per day and the other group took placebo; the intervention duration was 8 weeks. Anthropometric indices and metabolic factors were measured at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…80 Chromium 2-picolinate is one of the functional ingredients in health foods, which can reduce the glucose level and insulin resistance of diabetics. 81 These collectively support that vitamin D deficiency could affect the tryptophan metabolic pathway by gut microbiota, which could lead to impaired glucose tolerance. There was a sex difference in the effect of vitamin D deficiency on the beta diversity of gut microbiota, which was greater in males than in females.…”
Section: Food and Function Papermentioning
confidence: 80%
“…80 Chromium 2-picolinate is one of the functional ingredients in health foods, which can reduce the glucose level and insulin resistance of diabetics. 81 These collectively support that vitamin D deficiency could affect the tryptophan metabolic pathway by gut microbiota, which could lead to impaired glucose tolerance. There was a sex difference in the effect of vitamin D deficiency on the beta diversity of gut microbiota, which was greater in males than in females.…”
Section: Food and Function Papermentioning
confidence: 80%
“…No prior research has shown that all therapies significantly reduced insulin and HOMA-IR levels in T2DM models when given individually but substantially less when administered with PGZ + Cr-GTF compared to PL and PGZ. [ 21 ] PGZ with both Cr compounds improved FBG and HbA1c levels but did not improve pharmacological responsiveness.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, CP has been widely used in the fields of hypoglycemic functional foods and pharmaceuticals. In addition, CP has been confirmed to have a positive effect on diabetic complications, such as protecting diabetic atherosclerosis by inhibiting the expression of Thrombospondin-1, improving diabetic nephropathy and coronary heart disease through antioxidant and anti-inflammation effects [ 21 , 27 , 28 , 29 ]. Here we administered CP to diabetic rats for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%